2023
DOI: 10.1111/jir.13036
|View full text |Cite
|
Sign up to set email alerts
|

Promoting self‐determination of persons with severe or profound intellectual disabilities: a systematic review and meta‐analysis

Abstract: People with severe or profound intellectual disabilities (IDs) are believed to experience low levels of self‐determination, which negatively affects their quality of life. This systematic review describes existing interventions aimed to support self‐determination or components thereof and synthesises evidence on the interventions' effects. Eight databases were searched, turning in 76 articles for the final inclusion. The studies included 631 people with severe or profound IDs of whom 81% had multiple disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 120 publications
2
6
0
Order By: Relevance
“…To get insight into the dimensions of personals development and selfdetermination and how these are related to the basic psychological needs, we need to broaden our view of personal development and self-determination in people with pervasive support needs. In the current review, most studies report choice making as a concept that leads to enhanced self-determination (Kuld et al, 2023), which is in line with our findings, while some studies like Singh et al (2003) also looked at personal preferences. Although the underlining theories differ between the studies found, it is clear that technology has the potential to contribute to personal development and self-determination.…”
Section: Theoretical Reflectionssupporting
confidence: 88%
See 1 more Smart Citation
“…To get insight into the dimensions of personals development and selfdetermination and how these are related to the basic psychological needs, we need to broaden our view of personal development and self-determination in people with pervasive support needs. In the current review, most studies report choice making as a concept that leads to enhanced self-determination (Kuld et al, 2023), which is in line with our findings, while some studies like Singh et al (2003) also looked at personal preferences. Although the underlining theories differ between the studies found, it is clear that technology has the potential to contribute to personal development and self-determination.…”
Section: Theoretical Reflectionssupporting
confidence: 88%
“…which affects the way a relative or healthcare professional may look at development (Rees, 2017). Kuld et al (2023) concluded that most studies that focus on self-determination in people with pervasive support needs are limited to choice making and independence, which may not be a complete reflection of the basic psychological needs. According to the self-determination theory, competence, relatedness and autonomy are basic psychological needs that lead to development and enhance well-being (Deci & Ryan, 1985;Ryan & Deci, 2000).…”
Section: Theoretical Reflectionsmentioning
confidence: 99%
“…This observation is in line with existing evidence suggesting that samples recruited through social media tend not to be representative of the broader Autistic population (Rødgaard et al, 2022;Rubenstein & Furnier, 2021). It may also be the result of us not including intellectual disability as a search term in the review, as many studies that include Autistic participants with intellectual disability are subsumed within broader studies of "intellectual disability" (Blacher & Kasari, 2016;Thurm et al, 2019; see Kuld et al, 2023 for an example). It is also worth considering that people more invested in their Autistic identity may be more likely to take part in these studies than those for whom being Autistic is not a salient aspect of their identity.…”
Section: Limitationssupporting
confidence: 79%
“…For individuals with severe or profound intellectual disabilities (IDs), interventions aimed at supporting SD have shown positive effects. These interventions focus on components such as choice-making, independence, and problem-solving and include elements such as technology, training packages, and changes in policies and living arrangements (Kuld et al, 2023). Additionally, contextual variables such as living Journal of Disability Research 2024 environment and specialized supports play a significant role in the development of SD in individuals with IDs (Canlas et al, 2023;Vicente et al, 2023).…”
Section: At and Sdmentioning
confidence: 99%